Mirabegron in urinary incontinence in the aged: a systematic review - Karelius, Saana (fi=Turun yliopisto|en=University of Turku|, 2016)
The aim of this study was to systematically gather the evidence on the efficacy and safety of mirabegron and to compare them between aged and young people (people younger than 65 years old). A systematic review was used as a research method, the study search of which was applied to Pubmed (MEDLINE). In the search articles written in English were accepted. Only randomised controlled trials and open-label studies were used as material for this systematic review. As a result of a search 11 randomised controlled trials (RCT) and 3 open-label studies were found. Studies included participants, whose means of ages varied from 30.9 to 74.1 years. Only a few studies focusing on the adverse events of mirabegron handled separately participants under or over 65 years old. According to this systematic review, the symptoms of urinary incontinence can be reduced in the middle-aged and aged even at the dose of 25 mg of mirabegron. However, based on most of the studies it can be concluded that the dose of 50 mg of mirabegron is obviously the most effective dose and the results do not significantly improve with 100─300 mg doses of mirabegron. On the basis of this review it cannot be constated whether the efficacy of mirabegron is different between the young and the aged, since all of the efficacy studies focused on the middle-aged and aged population and the aged were not researched as an own group. Mirabegron proved to be a well tolerated medicine in the middle-aged and aged population, the number of people suffering from adverse events of mirabegron was quite similar to the number of suffering from those of placebo. However, some adverse events were more common with mirabegron, among these cardiovascular disorders, minor neurological symptoms, non-specific psychiatric disorders, gastrointestinal symptoms, infections and skin disorders. Nevertheless, on the basis of this review it is difficult to constate, whether safety of mirabegron is different in the aged and in the young population, since most of the safety studies involved focused on the middle-aged and aged participants.

Tutkimuksen tavoitteena oli kerätä systemaattisesti tietoa mirabegronin käytön tehokkuudesta ja turvallisuudesta virtsainkontinenssin hoidossa ja verrata näitä vanhusten ja nuorten (alle 65-vuotiaat) välillä. Tutkimusmenetelmänä käytettiin systemaattista katsausta. Systemaattisessa kirjallisuushaussa käytettiin PubMedtietokantaa. Haun tuloksena tutkimukseen mukaan otettiin 11 satunnaistettua, lumekontrolloitua tutkimusta ja 3 avointa tutkimusta, jotka oli julkaistu englanniksi. Tutkimuksiin osallistujien keski-iät vaihtelivat välillä 30,9-74,1 vuotta. Alle 65-vuotiaat oli eroteltu omaksi ryhmäkseen vain muutamassa mirabegronin haittoja käsittelevässä tutkimuksessa. Tämän systemaattisen katsauksen mukaan jo 25 mg annos mirabegronia voi vähentää virtsainkontinenssin oireita keski-ikäisillä ja vanhuksilla. Useimpien tutkimusten perusteella voidaan kuitenkin todeta, että mirabegronin annos 50 mg on selvästi tehokkain annos ja hoitotulokset eivät merkitsevästi parane 100─300 mg annoksilla. Johtopäätöksiä mirabegronin tehon eroista nuorilla ja iäkkäillä ihmisillä ei voi kuitenkaan tämän tutkimuksen perusteella tehdä, koska kaikki tehotutkimukset keskittyivät keski-ikäisiin ja iäkkäisiin ihmisiin ja iäkkäitä ei oltu erotettu omaksi ryhmäkseen. Mirabegroni osoittautui keski-ikäisillä ja vanhuksilla hyvin siedetyksi lääkkeeksi. Jotkin haittavaikutukset olivat kuitenkin mirabegronia käytettäessä yleisempiä kuin lumetta käytettäessä, muiden muassa sydän- ja verisuonioireet, lievät neurologiset oireet, tarkemmin määrittelemättömät psykiatriset oireet, mahasuolikanavan oireet, infektiot, ja iho-oireet. Tämän tutkimuksen perusteella on kuitenkin vaikea todeta, ovatko mirabegronin sivuvaikutukset erilaisia vanhuksilla ja nuorilla ihmisillä, koska suurin osa mirabegronin haittoihin keskittyneistä tutkimuksista keskittyi keski-ikäisiin ja iäkkäisiin ihmisiin.
Mirabegroni virtsainkontinenssissa vanhuksilla: systemaattinen katsaus